Recent trends in the youth labor market in Colombia: Diagnosis and policy challenges - Andrés Ham; Darío Maldonado; Carlos Santiago Guzmán-Gutiérrez (IZA Journal of Labor Policy, 2021)
This paper characterizes the labor market of youth in Colombia from 2008 to 2017. We estimate labor market indicators for individuals aged between 14 and 28 years using microdata from Colombia's household surveys over the study period. Our estimates document the main patterns and trends in the labor market of youth in labor force participation, employment, unemployment, informality, and earnings. We compare these statistics with the same indicators of adults (individuals aged between 29 and 65 years), and explore differences in characteristics within youth such as gender, region, educational attainment, socioeconomic status (SES), and experience. Results indicate that participation rate of young Colombians have increased in recent years, but are mainly employed in low-quality jobs namely unsalaried and informal. We also document marked inequalities in labor market outcomes across youth characteristics. We provide a series of recommendations to guide future youth labor policy based on these estimates as well as the critical analysis of recent youth policies in Colombia.
Keywords: J08; J13; J21; J24; O17; 330; youth; labor market; transition into the labor market; labor policy; Colombia